Rozkład naprężeń w nieskończonej płycie złożonej - S.K. Chakrabarti (Engineering Transactions)
The expressions for stresses and displacements in two semi-infinite isotropic plates connected together, having different elastic properties and acted on by a ouple at any point inside one of them, have been obtained in this paper.